Fibronectin in periodontal health and disease - A G Manimegalai (Journal of Orofacial Sciences, 2016)
Fibronectin is a main component of connective tissue and has various biologically significant roles to play in tissue integrity, remodelling and repair, apart from influencing pathological processes. This review looks into the physiology of fibronectin and its influences in health and disease.